2015
DOI: 10.1016/j.jbiomech.2015.02.064
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical properties of murine meniscus surface via AFM-based nanoindentation

Abstract: This study aimed to quantify the biomechanical properties of murine meniscus surface. Atomic force microscopy (AFM)-based nanoindentation was performed on the central region, proximal side of menisci from 6-to 24-week old male C57BL/6 mice using microspherical tips (R tip ≈ 5 μm) in PBS. A unique, linear correlation between indentation depth, D, and response force, F, was found on menisci from all age groups. This non-Hertzian behavior is likely due to the dominance of tensile resistance by the collagen fibril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 49 publications
7
43
2
Order By: Relevance
“…The effective moduli of the Sham knee menisci were similar to our previously reported values of age-matched, normal murine menisci. 24 By contrast, for the synovium, histology did not reveal appreciable signs of inflammation and hyperplasia, such as synovial lining thickening, increased cellularity or inflammatory cell infiltration (Fig. 6b).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The effective moduli of the Sham knee menisci were similar to our previously reported values of age-matched, normal murine menisci. 24 By contrast, for the synovium, histology did not reveal appreciable signs of inflammation and hyperplasia, such as synovial lining thickening, increased cellularity or inflammatory cell infiltration (Fig. 6b).…”
Section: Resultsmentioning
confidence: 87%
“…23 Comparing the modulus measured at the same rate amongst different conditions, such as Sham versus DMM, can therefore identify relative differences in their mechanical behaviors. In addition, following the same procedure, 24 nanoindentation was performed on the non-ossified, central region, proximal surfaces of medial and lateral menisci at 8 weeks after surgery ( n = 5).…”
Section: Methodsmentioning
confidence: 99%
“…Since commercial nano-indenters recently became readily available, nano-indentation has been widely used for the characterization of cartilage. 16, 24, 33 When the indenter size is on the same scale as collagen fibrils or chondrocytes, 10 the continuum assumption is no longer valid, and the technique developed here is therefore not suitable for estimation of mechanical properties at the nano-scale. Secondly, articular cartilage has a much more complicated structure than that described by the two nonlinear models here.…”
Section: Discussionmentioning
confidence: 99%
“…25 When cartilage is treated as linear elastic material, the Hertzian contact solution on an infinite half space is widely used, which is specifically suitable for nano- or micro-indentation tests. 24 For larger-scale indenters, Hayes solution 17 is often used since it removes the infinite half-space assumption in the Hertzian contact problem. In the early 1980's, Mow and coworkers 32 developed a porous elastic model for articular cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…Using such methods, Danso et al (2015) suggested that the medial meniscus is more inhomogeneous than the lateral meniscus and that the nonlinearities in material properties are due to the density of collagen fibers and the associated fluid content. In contrast, it would appear that the surface layer of the meniscus is relatively homogeneous (Li et al, 2015) and poro-viscoelastic, unlike the deep zones of the tissue. Wheatley et al (2015) utilized the inverse FE approach to demonstrate that menisci subjected to a traumatic compressive load had decreased material properties at twelve weeks post-impact compared to control.…”
mentioning
confidence: 91%